2021
DOI: 10.1007/s10815-020-02046-4
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and pregnancy outcome among women undergoing assisted reproductive technology treatment in Windhoek, Namibia

Abstract: Purpose Infertility has been defined as a couple's failure to conceive after regular and unprotected coitus for 1 year or six months, depending on the age of the female counterpart. Although infertility can result from both the male and/or the female, often the female partner faces pressure since it is believed in some African cultures that a woman without children is like a tree without leaves. The aim of this study was to determine the prevalence of successful pregnancy outcomes among infertile women undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Assisted reproduction technologies (ART) include ovulation induction, IVF, and subsequent embryo transfer to the uterus, and treatment with exogenous human chorionic gonadotropin or progesterone [9] .…”
Section: Highlightsmentioning
confidence: 99%
“…Assisted reproduction technologies (ART) include ovulation induction, IVF, and subsequent embryo transfer to the uterus, and treatment with exogenous human chorionic gonadotropin or progesterone [9] .…”
Section: Highlightsmentioning
confidence: 99%
“…Mitochondrial activity in sperm is improved by Myo-Ins, which has a positive impact on a wide variety of sperm processes [239], including capacitation, acrosome response, and motility regulation. This results in an increase in the motility of sperm in patients who already have aberrant sperm parameters [240]. In this regard, Governini et al [241] demonstrated that sperm motility is noticeably enhanced following treatment with myo-Ins.…”
Section: Inositolsmentioning
confidence: 99%
“…In last few decades, it has been observed that couple avoids having parenthood before 35 years. Such delaying in family planning may affect female fertility [46][47][48][49] . If a couple not able to have a child even after having unprotected sex for more than a year should visit a medical center.…”
Section: Fertility Problemsmentioning
confidence: 99%